Validation of Serbian version of chronic obstructive pulmonary disease assessment test - Milenković, Branislava; Dimić Janjić, Sanja; Kotur-Stevuljević, Jelena; Kopitović, Ivan; Janković, Jelena; Stjepanović, Mihailo; Vukoja, Marija; Ristić, Snežana; Davičević-Elez, Žaklina (Vojnosanitetski pregled, 2021)
Background/Aim. The Chronic obstructive pulmonary disease (COPD) Assessment Test (CAT) is a simple and reliable tool designed to measure overall COPD related health status and complement physician assessment in routine clinical practice. Objective of this study was to evaluate the validity of the Serbian version of CAT. Methods. Study included 140 outpatients in the stable COPD, recruited from two centres: Clinic for Pulmonology, Clinical Center of Serbia, Belgrade, and Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica. All patients completed pulmonary function testing – spirometry, the CAT and the modified Medical Research Council (mMRC) dyspnea scale at baseline visit. The CAT test-retest reliability was tested in 20 patients by the same investigator (physician). Results. We demonstrated that Serbian version of CAT had high internal consistency with Cronbach’s alpha 0.88. Test-retest analysis showed good correlation between CAT scores in two time points (Spearman’s ρ = 0.681, p < 0.01). In our study the CAT correlated moderately to mMRC scale (ρ = +0.57), weakly to FEV1 (ρ -0.214), was positively related to number of exacerbations, but did not showed exact regularity with change in the Global Initiative for Chronic Obstructive lung disease (GOLD) stage. Conclusion. The Serbian version of CAT is a reliable, simple and easy-to-use tool that can be used in everyday clinical practice to assess the health status of COPD patients in Serbia.
Keywords: pulmonary disease, chronic obstructive; surveys and questionnaires; serbia; comorbidity; forced expiratory volume